Penerapan DFMA untuk Low Cost High Customization Product - Ilham Priadythama; Susy Susmartini; Alviandi Wahyu Nugroho (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
Design for Manufacturing and Assembly (DFMA) is a method to evaluate the design of productwith considering the ease of manufacture process and the assembly process. UNS LPPD Hand isprosthetic hand with the function and shape that has likely the original hand man. UNS LPPD Hand is developed by the Laboratory Planning and Product Design of Sebelas Maret University (Laboratorium P3 UNS). From the conceptual design of prosthetic finger by Cahyadin (2016), the prototype can't do the movement flexed according with the design objectives and there are some components that not required. Therefore, there are some components that must be modified or eliminated. The modified component is phalanx of media and eliminated components are short and long pin holder The result is improvement of design prosthetic finger that 2 components are fixed and 4 components are eliminated, and reducing the process from 99 steps to 79 steps